Synthesis of Polymerization of New Derivative of 2-Decanoic Acid Extracted from Coriander Seed - Fatimah Ali Hussein (Journal of Global Pharma Technology, 2019)
This work, includes preparation of the derivative of decanoic acid was extracted from conriander seeds by fractional distillation for four hours, then reacted with one groups of amin of thio urea the2nd group amin in thioureia was reacted with maleic anhydride a different drugs was used to obtain novel derivatives. The compounds written off as by using some spectroscopic methods, H1NMR and FT-IR used to characterization the derivatives, control drug release was studying of some derivatives, biological activity against bacterial was studying and thermal stability of the derivatives.Keywords: Decanoic acid, Conriander seeds, FT-IR, H1NMR